The dialog between mother and newborn: insights from immune mediator crosstalk elicited by antenatal SARS-COV-2 exposure - Canellas-de-Castro, Maria Eduarda; Sasaki, Lizandra Moura Paravidine; Fernandes, Geraldo Magela; Motta, Felipe; Alves de Araújo Júnior, David; Schulte, Heidi Luise; Silva, Ângelo Pereira da; Alves, Caroline de Oliveira; Tristão, Rosana Maria; Jesus, José Alfredo Lacerda de; Costa, Karina Nascimento; Castro, Luiz Claudio Gonçalves de; et al. (Frontiers in Immunology, 2025)
GoalThe present study intended to evaluate whether the profile of soluble immune mediators observed in cord blood samples resembles the pattern identified for mother serum samples.MethodsFor this purpose, parallel analysis of chemokines, cytokines, and growth factors was carried out in mother–newborn paired samples from acute and convalescent COVID-19 subgroups (Early, Intermediate, and Late) as well as healthy controls (HC).ResultsData demonstrated that increased levels of CCL11, IFN-γ, IL1-Ra, and G-CSF were observed in cord blood samples from most COVID-19 subgroups, with fold change magnitude from 1.6× to 8.2× as compared with HC. Comparative analysis of mother–newborn pairs demonstrated that several immune mediators (CCL11, CCL4, IFN-γ, PDFG, and G-CSF) exhibited high increment magnitude in cord blood as compared with mother serum, reaching values up to 15.7×, mainly at convalescent COVID-19 infection. The signatures of soluble immune mediators revealed distinct waveforms for cord blood and mother serum, with a waning of immune mediators in the latter, contrasting with the increasing set of molecules in the former from acute toward convalescent COVID-19. Integrative network analysis of immune mediators in mother–newborn pairs showed an increase of neighborhood connectivity both in microenvironments and in their interplay from acute toward late convalescent COVID-19. Our results support the hypothesis of the interplay between mother serum and cord blood microenvironment that may impact the fetus development.ConclusionTogether, this evidence regarding the maternal–fetal crosstalk can ultimately subsidize the improvement of clinical practice and public health policies for management of prenatal exposure to SARS-CoV-2 infection.